Factors associated with ventilatory failure in obesity - Manuel, A (2016)
INTRODUCTION: Only a third of obese patients develop chronic ventilatory failure. This cross-sectional study assessed multiple factors potentially associated with chronic ventilatory failure. MATERIALS/PATIENTS AND METHODS: Participants had a body mass index (BMI) >30 kg/m(2), with or without chronic ventilatory failure (awake arterial partial pressure of carbon dioxide >6 kPa or base excess (BE) =2 mmols/L). Factors investigated were grouped into domains: (1) obesity measures, (2) pulmonary function, (3) respiratory and non-respiratory muscle strength, (4) sleep study derivatives, (5) hypoxic and hypercapnic responses, and (6) some hormonal, nutritional and inflammatory measures. RESULTS: 71 obese participants (52% male) were studied over 27 months, 52 (SD 9) years and BMI 47 (range 32-74) kg/m(2). The best univariate correlates of BE from each domain were: (1) dual-energy X-ray absorptiometry measurement of visceral fat (r=+0.50, p=0.001); (2) supine forced expiratory volume in 1 s (r=-0.40, p=0.001); (3) sniff maximum pressure (r=-0.28, p=0.02); (4) mean overnight arterial oxygen saturation (r=-0.50, p<0.001); (5) ventilatory response to 15% O2 breathing (r=-0.28, p=0.02); and (6) vitamin D (r=-0.30, p=0.01). In multivariate analysis, only visceral fat and ventilatory response to hypoxia remained significant. CONCLUSIONS: We have confirmed that in the obese, BMI is a poor correlate of chronic ventilatory failure, and the best independent correlates are visceral fat and hypoxic ventilatory response.